FENOFIBRATE ADMINISTRATION DOES NOT AFFECT MUSCLE TRIGLYCERIDE CONCENTRATION OR INSULIN SENSITIVITY IN HUMANS - Perreault, Leigh (2011)
OBJECTIVE: Animal data suggest that males, in particular, rely on PPAR-α activity to maintain normal muscle triglyceride metabolism. We sought to examine whether this was also true in men vs. women and its relationship to insulin sensitivity. MATERIALS/METHODS: Normolipidemic obese men (n=9) and women (n=9) underwent an assessment of insulin sensitivity (IVGTT) and intramuscular triglyceride metabolism (GC/MS and GC/C/IRMS from plasma and muscle biopsies taken after infusion of [U-13C]palmitate) before and after 12 weeks of fenofibrate treatment. RESULTS: Women were more insulin sensitive (Si; 5.2(0.7 vs. 2.4(0.4 ×10−4/uU/ml, W vs. M, p<0.01) at baseline despite similar intramuscular triglyceride (IMTG) concentration (41.9(15.5 vs. 30.8(5.1 ug/mg dry weight, W vs. M, p=0.43), and IMTG fractional synthesis rate (FSR; 0.27(0.07 vs. 0.35(0.06/hr, W vs. M, p=0.41) as men. Fenofibrate enhanced FSR in men (0.35(0.06 to 0.54(0.06, p=0.05), with no such change seen in women (0.27(0.07 to 0.32(0.13, p=0.73), and no change in IMTG concentration in either group (23.0(3.9 in M, p=0.26 vs. baseline; 36.3(12.0 in W, p=0.79 vs. baseline). Insulin sensitivity was unaffected by fenofibrate (p>0.68). Lower percent saturation of IMTG in women vs. men before (29.1(2.3 vs. 35.2(1.7%, p=0.06) and after (27.3(2.8 vs. 35.1(1.9%, p=0.04) fenofibrate most closely related to their greater insulin sensitivity (R2=0.34, p=0.10), and was largely unchanged by the drug. CONCLUSIONS: PPAR-α agonist therapy had little effect on IMTG metabolism in men or women. IMTG saturation, rather than IMTG concentration or FSR, most closely (but not significantly) related to insulin sensitivity and was unchanged by fenofibrate administration.